The Effect of Bone Mineral Density on Quality of Life in Men with Osteoporosis - Yalkın Çalık; Ayça Filiz Çalık (Galenos Yayinevi, 2015)
Objective: Osteoporosis (OP) is a metabolic bone disease characterized by low bone mass and microarchitectural deterioration of bone tissue. OP is an important health problem with regard to morbidity, mortality, and negative effects on quality of life (QOL). The aim of this study was to evaluate the effect of bone mineral density (BMD) on QOL in men with osteoporosis. Materials and Methods: A total of 180 male patients aged between 40-60 years admitted to Bolu Physical Therapy and Rehabilitation Hospital were included in the study. 113 patients (mean age: 50.01±5.01 years) diagnosed with OP according to BMD values at the lumbar spine (L1-L4) and the femur neck measured using Dual Energy X-Ray absorptiometry were formed the case group, 67 patients (mean age: 44.62±3.86 years) not diagnosed with OP were formed control group. A questionnaire prepared for assessment of sociodemographic features and risk factors for osteoporosis was applied in both groups after they gave their consent. The quality of life was assessed by means of Quality of Life Questionnaire of the European Foundation for Osteoporosis (QUALEFFO) and Short Form-36 (SF-36). In the statistical analysis student's t test and correlation analyses were performed by using SPSS 11.0 computer program and p<0.05 was considered statistically significant. Results: Both femoral neck and lomber spine bone mineral density was lower in the case group than that of the control group (p<0.001). According to QUALEFFO and SF-36 scores, OP was found to reduce the quality of life (p<0.001). Smoking, bone fracture and inadequate daily calcium intake have negative effects on quality of life in the case group (p<0.05). Conclusion: Quality of life was influenced by numerous variables. These results point out that osteoporotic patients should be evaluated multidimensionally and different approaches are needed to improve their quality of life. (Turkish Journal of Osteoporosis 2015;21: 10-4)